Environmental Factors Associated with Mosquito Vector Larvae in a Malaria-Endemic Area in Ratchaburi Province, Thailand - Tanawat Chaiphongpachara; Prasit Yusuk; Sedthapong Laojun; Chaekki Kunphichayadecha (The Scientific World Journal)
Malaria is transmitted by female mosquitoes in the genus Anopheles and is a major public health issue. Different species of Anopheles mosquitoes have different epidemiological characteristics, behaviors, and ecological requirements, and so an understanding of their biology and ecology in a particular area is critical for successful disease control. The aim of this study was to determine which environmental factors are associated with Anopheles larvae in a malaria-endemic area in Ratchaburi Province, Thailand, which shares a border with Myanmar. In October 2016, we collected mosquito larvae and measured six environmental factors at 10 study sites located along Lam Pachi River, which flows through Huay Nam Nak village in Ratchaburi Province. We found two species of Anopheles larvae (An. subpictus sensu lato (s.l.) Grassi and An. barbirostris s.l. van der Wulp) at 7 of the 10 study sites, the numbers of which significantly differed between sites (p < 0.05). Pearson correlation analysis showed that the numbers of larvae of both species were significantly positively correlated with the dissolved oxygen level (p < 0.01) and significantly negatively correlated with the width of the river (p < 0.05) and pH (p < 0.01). By contrast, turbidity, water depth, and water temperature were not associated with larval abundance. Mosquito species which belong to genus Anopheles are considered to be of public health and medical importance. Therefore, Anopheles mosquito surveillance and control in the study sites are essential. This information will facilitate vector-borne disease control and improve our understanding of the biology of Anopheles vectors in rivers located along international borders, further reducing the number of patients in this malaria-endemic area.